Peran Guru Berubah, Profesionalisme Berkembang: Masa Depan Pendidikan Korea dan Indonesia: Peran Guru Berubah, Profesionalisme Berkembang: Masa Depan Pendidikan Korea dan Indonesia - Suk Young Ji; Sophia Tri Satyawati; Yari Dwikurnaningsih (Program Studi S1 PG-PAUD, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Satya Wacana, 2025)
The rapidly changing 21st-century society demands fundamental changes in the educational paradigm, centered on the redefinition of the teacher's role. Moving beyond mere transmitters of knowledge, teachers are now expected to become facilitators, mentors, and collaborators who unleash students' potential and foster critical thinking and creativity. This study aims to analyze the comparison of the early childhood education (PAUD) systems in Indonesia and South Korea based on four main focuses: (1) the PAUD education system, (2) the paradigm of the teacher's role, (3) teacher professional development, and (4) the transformation of digital technology in learning. This study is a literature review of ten scientific articles published from 2019–2024 from national and international journals. The results of the review indicate that both countries have the same policy direction in strengthening child-centered education and teacher professionalism, but are at different levels of implementation. South Korea has reached the stage of institutionalizing a digitally integrated and teacher-oriented PAUD system, while Indonesia is still focused on increasing basic capacity and equalizing access. These findings recommend the need for a continuous professional development system, digital literacy teachers, and cross-sectoral policies to support the transformation of early childhood education in Indonesia towards global standards.